Dangerously Neglecting Courtroom Realities. Issue 1 (14th October 2016) - Smeets, Tom; Merckelbach, Harald; Jelicic, Marko; Otgaar, Henry
Summary: Brewin and Andrews recently argued that expert witnesses should be cautious when informing the legal arena about the potential for false memories. We argue that memory researchers—whose studies often were inspired by miscarriages of justice due to erroneous statements provided by witnesses, victims, or defendants—can and should emphasize the base rates of false memories. After all, even if Brewin and Andrews' estimate of 15% is an accurate higher bound estimate of false memories in real life cases, neglecting the science of false memories could lead to many more unnecessary miscarriages of justice. Copyright © 2016 John Wiley & Sons, Ltd.